Estudio sobre la concesión de los arraigos en relación a la prisión preventiva en la ciudad de Ibarra - Bastidas Figueroa, Cristian Santiago (2024)
The study on the granting of social ties in relation to pretrial detention in the city of Ibarra is of great relevance as it sheds light on the application of precautionary measures in the Ecuadorian justice system. The qualitative research reveals the complexity and inherent tensions in the granting of social ties and its connection to pretrial detention in the country's legal context. Emphasizing the importance of proportionality, case individualization, and exploration of less restrictive alternatives, it urges a reconsideration of approaches to achieve a fairer and more equitable criminal justice system, in line with ethical and philosophical principles aimed at preserving citizens' freedom. The findings show that the criteria used to demonstrate social ties in the city of Ibarra are varied and do not always comply with current regulations, potentially resulting in the violation of the rights of individuals undergoing legal proceedings. Therefore, a comprehensive review of these criteria is recommended to ensure their conformity with legal standards and the unrestricted respect for the rights of those involved in criminal processes. This critical analysis contributes to expanding theoretical knowledge about the effectiveness of social ties and the parameters used by judges, lawyers, and legal professionals in criminal matters, providing a solid foundation for future research and promoting a more equitable and transparent justice system in Ecuador. Additionally, it highlights the need to consider alternatives to pretrial detention where feasible, which could help reduce prison overcrowding and improve penitentiary management in the country.